GaAs(1-x)Bix: A Promising Material for Optoelectronics Applications. Issue 3 (4th May 2017) - Nagaraja, Kodihalli K.; Mityagin, Yuri A.; Telenkov, Maksim P.; Kazakov, Igor P.
ABSTRACT: Bismuth alloying with GaAs has promised greater advantages in the realization of more convenient mid and near IR photonic devices owing to its novel and unique properties. The coexistence of faster band gap reduction and a strong increase in spin-orbit splitting energy with an increase in Bi concentration is one of those. However, the realization of practical devices is hindered due to several critical issues associated with the electronic properties of this material. Many of these limitations primarily arise due the difficulty obtaining high-quality structures. In this article, we review the growth and properties of GaAs (1−x) Bi x . We have provided a comprehensive study of the properties by considering both from a fundamental perspective and also on their potential device applications.